Language Curriculum and Material Development: A Book Review - Andi, Adisaturrahimi (Jurnal Ilmu Sosial dan Humaniora, 2023)
A book review is a type of literary criticism in which the merit, style, and content of a book are evaluated. Language curriculum design is becoming increasingly important these days. This is supported by a number of authors who have written books on language curriculum design, one of which is "Language Curriculum Design" by I.S.P. Nation and John Macalister, which serves as a primer for all students to teach them about the best practices in language curriculum design. This book consists of fourteen chapters. Among these chapters, there are two chapters that explain the language curriculum design generally, while the rest of the chapters explained specifically. Moreover, all the chapters provide some aspects that occur in language curriculum design. Every point successfully guide the readers to understand the process of designing language curriculum. It helps the teachers and lecturers to design the curriculum that suits with the students needs. The presentation of each chapter is clear yet the content is easy to understand. The summary is given in every chapter even successfully becomes a guideline for teachers and students to understand how each topic relates with the previous chapter. Overall, this book is helpful for people who want to teach their students in creative methods and transition their classroom to a more student-centered environment.